National Health Insurance: what now, what later, what never? - Pauly, Mark V.; American Enterprise Institute for Public Policy Research (Washington, D.C.: American Enterprise Institute for Public Policy Research, 1980)
This publication is divided into four parts. Part one treats the political and economic concerns of initiating a national health insurance program. Parts two and three review the solution to the problem of underinsurance and over-insurance. Part four discusses cost containment: long and short-run strategies.
Proceedings of a conference held by AEI's Center for Health Policy Research in Washington, D.C.
Includes bibliographical references.
ne 14/05/2018
Loan
Keywords: National health insurance; Medical care